Thermal Conductivity and Viscosity Correlations in Different Kinds of Aqueous Surfactant Solutions at Atmospheric Pressure as a Function of Temperature - Altun, Aycan; Şara, Osman Nuri (Springer/Plenum Publishers, 2021)
Surfactants with a wide range of uses are often preferred to reduce particle aggregation in nanofluid and provide stability. However, added surfactants affect the properties of not only nanofluids but also base fluids. In this study, binary mixtures were prepared by using water and three different surfactants, namely, SDS, Tween 80, and NP 10, in four different concentrations of 0.2 % to 0.8 % by weight, separately. Density, thermal conductivity, and viscosity values of these prepared mixtures were measured experimentally at atmospheric pressure and the temperature of 298 to 338 K. Then, correlations were derived with respect to the data obtained for the studied parameter ranges. According to the result, a quadratic polynomial with coefficients was fitted for the density equation and two models for viscosity behavior were derived. Moreover, Thermal conductivity correlations were developed as second-order polynomials of temperature and concentration function. The proposed correlations showed good agreement with our experimental results.
Keywords: Surfactant; Correlation; Density; Viscosity; Thermal conductivity